A Study of Sociological Issues in "Sonny’s Blues" - Sharma, Min Prasad; Upadhyaya, Parthivendra (Bhairahawa Campus Journal, 2023)
This research paper examines the sociological aspects and impact of blues in James Baldwin's "Sonny's Blues." Utilizing a sociological criticism approach, the study analyzes the dynamics of blues in the story and explores the dystopian environment of Harlem, highlighting the suffering experienced by Sonny and other black youths. The theoretical perspective applied emphasizes the relationship between the author and the text, contextualizing it within the social and cultural milieu. Through a close examination of the narrative, the paper reveals the role of blues as a means of expression and resilience for black Americans, transcending their collective experience. The findings underscore the significance of cultural heritage and the power of music in overcoming adversity. The research provides valuable insights into the societal issues faced by marginalized communities and emphasizes the importance of intra community harmony.